Public awareness and use of 997 emergency medical service phone number during the COVID-19 pandemic - Aljabri, Duaa; Albinali, Hissah (Frontiers in Public Health, 2022)
Background Emergency medical services (EMSs) are an important element of the healthcare system as it provides an opportunity to respond to critical medical conditions and save people's lives. In Saudi Arabia, EMS is offered via the EMS phone number “997” and mobile application “Asefny”. Methods This was an observational cross-sectional survey study exploring public awareness and use of the EMS phone number during the COVID-19 pandemic in Saudi Arabia. A bivariate analysis was performed to investigate factors affecting awareness and use of the EMS phone number and to compare the EMS acceptance to transport and timelines of ambulance arrival between requests made via the “997” EMS phone number and the “Asefny” mobile application during the country's emergency lockdown. Results A total of 805 participants were included in the analysis, where 66% reported awareness of the EMS phone number and 75% of them accurately identified the nature of the service provided by dialing the number. The men who participated, those with a bachelor's degree, with children, and with chronic conditions were more aware of the EMS phone number compared to the other participants. Of the total sample, 46.7% used EMS phone numbers at least one time (ever users). During the COVID-19 lockdown, the EMS accepted to transport 87% of the calls made by 997 phone number and 56.2% of the mobile application requests (P < 0.00). The ambulance arrived in ≤ 8 min in 53.6% of the 997 phone calls and 35.5% of the Asefny mobile requests (P < 0.00). Conclusions Findings showed commendable levels of awareness and the use of EMS phone numbers. However, the results suggest room for improvement by developing promotional and educational campaigns inspired by the factors identified as influential on both awareness and use. Mobile applications in EMS are promising to improve prehospital emergency service accessibility, which needs to be further investigated to assess its impact on the public health informatics experience.